Joana solved the equation 4x ^ 2 - 4x - 3 = 0 She followed the steps to solve a quadratic equation by grouping. However, in Step 3 she noticed that the two groupings did not share a common binomial, as shown in her work below. She concluded that the quadratic equation 4x ^ 2 - 4x - 3 = 0 has no solutionsIs Joana's conclusion correct ? Review Joana's work to answer the question Step 1: 4x ^ 2 + 2x + (- 6x) - 3 = 0 Step 2: (4x ^ 2 + 2x) + (- 6x - 3) = 0 Step 3: x(4x + 2) + (- 3(2x + 1)) = 0 ( 1 point) Yes, because the two groupings do not share a common binomial Yes, because there are no factors of -12 that add up to -4 No, because she can still continue the steps even if the two groupings have no shared binomial No, because she did not factor out the GCF from the first grouping

1 answer

Joana's conclusion is incorrect. The presence of a common binomial is not necessary for solving a quadratic equation by grouping. She can still continue with the steps even if the two groupings do not share a common binomial. The correct answer would be: No, because she can still continue the steps even if the two groupings have no shared binomial.
Similar Questions
    1. answers icon 1 answer
  1. 10.Joana solved the equation 4x2 − 4x − 3 = 0 . She followed the steps to solve a quadratic equation by grouping. However,
    1. answers icon 1 answer
  2. A student solved the following equation using the following steps:2(2x + 2) = 4(x + 4) 4x + 4 = 4x + 4 4 = 4 Infinite solutions
    1. answers icon 1 answer
  3. 5. A student solved the following equation using the following steps:2(2x+2)=4(x+4) 4x+4=4x+4 4=4 Infinitely many solutions (2
    1. answers icon 29 answers
more similar questions